Valuations that lead to declare the unenforceability of judicial sentences in the civil process - Espíritu Arteta, Evi (2019)
Throught of a judicial judgment coated with the quality of res judicata, it seeks to resolve a conflict of interests, and it precisely that being fulfilled on their own terms makes effective the right to effective judicial protection; however, there are material and legal circumstances that can modify the context in which the judgment was issued, which entails a declaration of the unenforceability of the same, since trying to execute a sentence that has an impossibility in its execution would become arbitrary and contrary to a criterion of reasoning linked to justice, which is the essence of the Constitutional State of Law.